The importance of conserving Mexico's tomato agrodiversity to research plant biochemistry under different climates. Issue 6 (12th August 2021) - Sandoval‐Ceballos, María Guadalupe; Kalungwana, Ng' Andwe; Griffin, Jonathan Henry Charles; Martínez‐Guerra, Geovanni; Ramírez‐Ramírez, Iván; Maldonado‐Peralta, Ramiro; Marshall, Lisa; Bosch, Christine; Cruz‐Huerta, Nicacio; Gonzalez‐Santos, Rosalinda; León, Patricia; Chávez‐Servia, José Luis; et al.
Societal Impact Statement: Tomatoes are important to agriculture, human nutrition and cuisines globally. However, many commercial tomato varieties, including the saladette that dominates the North American market, are highly sensitive to environmental changes that impact yields and critical biochemical pathways including carotenoids and isoprenoids that influence nutritional content and flavour. We highlight the potential of tomato agrodiversity, notably its genetic diversity, as an undervalued research tool for understanding environmental regulation of plant biochemistry under different climates. Yet, tomato genetic diversity in Mexico, the major centre of tomato domestication, is not formally described or protected. We propose that transdisciplinary efforts are essential to identify, conserve and research these globally significant genetic resources. Abstract : Tomatoes are important to agriculture, human nutrition and cuisines globally. However, many commercial tomato varieties, including the saladette that dominates the North American market, are highly sensitive to environmental changes that impact yields and critical biochemical pathways including carotenoids and isoprenoids that influence nutritional content and flavour. We highlight the potential of tomato agrodiversity, notably its genetic diversity, as an undervalued research tool for understanding environmental regulation of plant biochemistry under different climates. Yet, tomato genetic diversity in Mexico, the major centre of tomato domestication, is not formally described or protected. We propose that transdisciplinary efforts are essential to identify, conserve and research these globally significant genetic resources.